2009
DOI: 10.4141/cjps08148
|View full text |Cite
|
Sign up to set email alerts
|

Association of seed and agronomic traits with isoflavone levels in soybean

Abstract: . 2009. Association of seed and agronomic traits with isoflavone levels in soybean. Can. J. Plant Sci. 89: 477Á484. Soybean, Glycine max (L.) Merr., seeds contain isoflavones, compounds with potential human health benefits. This study investigated the association of seed and agronomic traits with isoflavone level in a genetically diverse group of soybean genotypes to provide more information for cultivar development. F 4:7 lines derived from several crosses were grown in four locations in 2005 and six location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…As a quantitative trait controlled by many minor genes [192], isoflavone content in soybean seed largely depends on the environment [185,[193][194][195], to the extent that even the smallest changes in the microclimate can cause significant changes in the isoflavone contents. For example, it is reported that lower temperatures during the seed fill period increase the isoflavone content, whereas environments which were warmer and drier resulted in lower isoflavone contents [196][197][198][199]. In 76 environments during 12 years, Carrera and Dardanelli [200] found a 91% decrease in total isoflavone content with mean temperatures during the seed development rising from 14.1 to 26.7°C.…”
Section: Isoflavonesmentioning
confidence: 99%
See 4 more Smart Citations
“…As a quantitative trait controlled by many minor genes [192], isoflavone content in soybean seed largely depends on the environment [185,[193][194][195], to the extent that even the smallest changes in the microclimate can cause significant changes in the isoflavone contents. For example, it is reported that lower temperatures during the seed fill period increase the isoflavone content, whereas environments which were warmer and drier resulted in lower isoflavone contents [196][197][198][199]. In 76 environments during 12 years, Carrera and Dardanelli [200] found a 91% decrease in total isoflavone content with mean temperatures during the seed development rising from 14.1 to 26.7°C.…”
Section: Isoflavonesmentioning
confidence: 99%
“…Nevertheless, isoflavone broad-sense heritability was estimated to range from moderate [207] to high [192], indicating that genotype effects were high enough to enable efficient improvement of isoflavone contents [194,208]. The predominance of genotype effects over environmental was confirmed by Gutierrez-Gonzalez et al [192], Murphy et al [199] and Hoeck et al [206]. Successful high-isoflavone cultivar development necessitates investigating the relationships between isoflavones and other important traits.…”
Section: Isoflavonesmentioning
confidence: 99%
See 3 more Smart Citations